(3GbJUGOGJ GdfbhO h GdJehjds - (3RjfH MSjf(B, (3YhV Gddgs ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2010)
(3GdfbhO h GdfXGe GdfbOj(B- (3JWhQ GdfbhO h GgejJgG(B- (3GdfXGe GdfbOj(B- (3GdeDSSGJ GdfbOjI h GdeGdjI(B- (3GdEFJeGf(B- (3GdHfhc GdJLGQjI(B- (3GdHfc GdeQcRj(B- (3GdeDSSGJ GdfbOjI h GdeGdjI GdhSjWjI(B- (3GdHhQUGJ(B- (3GdfbhO h GdeJZjQGJ GdGbJUGOjI(B- (3bjeI GdfbhO ef NdGd GdJMdjd GdfbOj(B- (3GdfbhO h GdJVNes
Keywords: (3GdEbJUGO GdfbOjs; (3GdJehjds; (3GdfbhOs